ANALYTICAL NETWORK PROCESS BERBASIS KRITERIA MAJEMUK DALAM PEMILIHAN KARYAWAN UNTUK PROMOSI JABATAN - Amin, Ruhul (BINA INSANI ICT JOURNAL; Vol 1 No 2 (2014): Bina Insani ICT Journal (Agustus 2014), 2014)
The development of information technology in the era of rapid globalization causes a decision-making is very important in determining the decisions that must be taken in dealing with problems in the world of work. Decisions can be influenced by several aspects, this really influences the speed in taking decisions by the decision maker, where the decisions have to be quick and accurate. This research was made using the Analytical Network Process (ANP). Where is this algorithm do the counting process to find the best decision, that is by calculating the value of these criteria and compares them with the calculation of each possible decision to be taken. This research will be used in assisting the decision maker in determining which employees are promoted to promotion. Criteria used in promotion in accordance with existing procedures in the PT. Bridgestone Tire Indonesia. From the researchbased Decision Model Multi Criteria In Employee Selection For Promotion Using Analytical Network Process (ANP). Decision Support System will make the right decisions and be flexible with aspects that affect these decisions, and generate reports to the decision maker to help the decision maker in making decisions. Kata Kunci: Analytical Network Process, ANP, Promosi jabatan, Decision Support System, DSS.